Fifty shades of brown: Macroevolution of plumage brightness in the Furnariida, a large clade of drab Neotropical passerines. (14th March 2019) - Marcondes, Rafael S.; Brumfield, Robb T.
Abstract: Both natural and sexual selection are thought to affect the evolution of bird color. Most studies of the topic have focused on sexually dichromatic taxa and showy plumages, which are expected to be more influenced by social selection and usually result in increased conspicuousness. However, many bird clades display dull brown or gray plumages that vary greatly in brightness (lightness), but little in hue (shade). Here, we examine the macroevolution of brightness in one such clade, the Furnariida. We make comparisons across light environments, body parts, monochromatic lineages, and each sex of dichromatic lineages. We found that support for models including light environments is greater for the dorsum than for the venter, and that brightness evolution is more constrained in the former than in the latter. Plumages in this clade have evolved to be darker in darker habitats, consistent with natural selection for increased crypsis. Finally, the features of brightness macroevolution are broadly similar across the sexes of the dichromatic clade, challenging the view that sexual dichromatism is driven by different evolutionary processes acting in each sex. We conclude that, in the Furnariida, light environments and dorsal–ventral variation are more important than sex as axes of color evolution.